Παράγοντες επιτυχημένης εφαρμογής αγροτικών πολιτικών με έμφαση στην προστασία του περιβάλλοντος. Η περίπτωση της πολιτικής πολλαπλής συμμόρφωσης στην ελαιοκαλλιέρεγεια στη Μεσσηνία. - Ματσατσίνης, Ιωάννης (2015)
Today, the environmental policy is integrated into all EU policies. The measures of cross-compliance are a political tool of integrating environmental policy in the recently restructured Common Agricultural Policy. This dissertation examines the effectiveness of implementation of cross-compliance measures and the success of environmental objectives in olive cultivation in Messinia.